Peripheral G protein‐coupled inwardly rectifying potassium channels are involved in δ‐opioid receptor‐mediated anti‐hyperalgesia in rat masseter muscle. (6th June 2013) - Chung, M‐K.; Cho, Y.S.; Bae, Y.C.; Lee, J.; Zhang, X.; Ro, J.Y.
Abstract Background Although the efficacy of peripherally administered opioid has been demonstrated in preclinical and clinical studies, the underlying mechanisms of its anti‐hyperalgesic effects are poorly understood. G protein‐coupled inwardly rectifying potassium (GIRK) channels are linked to opioid receptors in the brain. However, the role of peripheral GIRK channels in analgesia induced by peripherally administered opioid, especially in trigeminal system, is not clear. Methods Expression of GIRK subunits in rat trigeminal ganglia (TG) was examined with reverse transcription‐polymerase chain reaction, Western blot and immunohistochemistry. Chemical profiles of GIRK‐expressing neurons in TG were further characterized. Behavioural and Fos experiments were performed to examine the functional involvement of GIRK channels in δ‐opioid receptor (DOR)‐mediated anti‐hyperalgesia under an acute myositis condition. Results TG expressed mRNA and proteins for GIRK1 and GIRK2 subunits. Majority of GIRK1‐ and GIRK2‐expressing neurons were non‐peptidergic afferents. Inhibition of peripheral GIRK using Tertiapin‐Q (TPQ) attenuated antinociceptive effects of peripherally administered DOR agonist, [D‐Pen2, D‐Pen6]‐enkephalin (DPDPE), on mechanical hypersensitivity in masseter muscle. Furthermore, TPQ attenuated the suppressive effects of peripheral DPDPE on neuronal activation in the subnucleus caudalis of the trigeminal nucleus (Vc) following masseteric injection of capsaicin. Conclusions Our data indicate that peripheral DOR agonist‐induced suppression of mechanical hypersensitivity in the masseter muscle involves the activity of peripheral GIRK channels. These results could provide a rationale for developing a novel therapeutic approach using peripheral GIRK channel openers to mimic or supplement the effects of peripheral opioid agonist.